PODEJŚCIE DO BŁĘDU W NAUCE JĘZYKÓW OBCYCH – PERSPEKTYWA UCZNIA - Ewa Półtorak, (Neofilolog, 2019)
The aim of the paper is to reflect on the problem of errors in the foreign language teaching-learning process from the learner’s perspective. The author proposes to investigate learners’ beliefs and opinions related to the role of errors in foreign language learning process. The problem will be discussed in the context of the teaching-learning process of French as a second language to adult beginners. The study was conducted among the students of the Institute of Romance Languages and Translation Studies at the University of Silesia. The data collected was analysed and divided into subject categories in order to provide an overall view of students’ beliefs and attitudes towards errors.